Evaluación de la aplicación de protocolos de bioseguridad en unidades de producción de cuyes en sectores priorizados de la Provincia de Cotopaxi - Escobar Reinoso, Stephany Silvana (2021)
The research was developed in five communities in the Cotopaxi province with the objective of evaluating the application of biosecurity protocols in guinea pig production units. The methodology is based on the Cronbach's alpha model with an absolute value of reliability and validity of 0.85 of the evaluation instruments, for the systematization of the data, the surveys were analyzed on the Google forms platform and their corresponding comparisons, it was made with the SPSS program. The results showed that 84.4% of people use footbaths, 65.6% are made of plastic, 75% of which are located on the outside, thus demonstrating the effect of the training in 96.9%. In reference to the use of disinfectants, quaternary ammonium obtains 50%. The 93.8% comply with the epidemiological control. They have demonstrated their organizational participation in local fairs with 56.3%, in zootechnical management they take into account age, weaning, type of feeding in 96.9%. As for the criteria for the selection of reproducers, 93.8% are based on zoometric measurements. This has determined that the beneficiaries generate 50% of genetic nuclei in the production systems. Concluding that there is a direct correlation among footbaths, training and knowledge, relating to the zootechnical management of animals, applying vaccination and deworming schedules as epidemiological control measures, linking training with the exchange of experiences in animal husbandry techniques and marketing plans to improve the rural economy.